Person and ethics of a psychiatrist during National Socialism: Friedrich Meggendorfer (1880–1953). Issue 1 (March 2020) - Braun, Birgit
Evaluation of sources not previously considered makes it possible to describe Friedrich Meggendorfer's role as a National Socialist university psychiatrist. Relevant archive material and literature were both assessed. The gene–hygiene affinity promulgated by Meggendorfer was based on his own scientific interests, early academic influences, and also positive reinforcement from his career choices. His application of scientific knowledge in the legitimization of National Socialist jurisdiction reflects a dark facet in Meggendorfer's life. One can also criticize his ethics in failing to use his eugenics expertise to stop 'euthanasia'. Future studies into the history of the ethical aspects of Nazi psychiatry should benefit from the setting up of criteria for the collection of biographical data. This would render comparisons and contrasts fairer and more stable.